2017
DOI: 10.7883/yoken.jjid.2015.464
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Human Immunodeficiency Virus, Hepatitis C Virus, and Syphilis Infection, and the Correlates of Sexually Transmitted Infections among Men Who Have Sex with Men in Zhenjiang, Jiangsu, China

Abstract: SUMMARY:A cross sectional survey was performed to investigate the epidemic of human immunodeficiency virus (HIV), hepatitis C virus (HCV), syphilis, and HIV-1 subtype infections among men who have sex with men (MSM) and to evaluate factors that were correlated with sexually transmitted infections (STIs) among 657 MSM in Zhenjiang, Jiangsu, during 2012Jiangsu, during -2013. Data on socio-demographic parameters and risky behaviors were collected, and blood samples were obtained. In this survey, the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…The trends of HCV infection among HIV-positive patients, however, remain less investigated in Asia-Pacific region that bears one-fifth of the global HCV burden [1]. While a recent study from Jiangsu, China did not reveal an increasing trend of HCV infection among MSM [14], several studies have demonstrated increasing trends of HCV infection among HIVpositive MSM in Hong Kong [15], Tokyo [16], and Taipei [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The trends of HCV infection among HIV-positive patients, however, remain less investigated in Asia-Pacific region that bears one-fifth of the global HCV burden [1]. While a recent study from Jiangsu, China did not reveal an increasing trend of HCV infection among MSM [14], several studies have demonstrated increasing trends of HCV infection among HIVpositive MSM in Hong Kong [15], Tokyo [16], and Taipei [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the Asia‐Pacific, sexual transmission of HCV has not been commonly reported. Recent studies in different cities in China have not shown increased or increasing HCV incidences among MSM . Needle‐sharing among injection drug users (IDUs) rather than male‐to‐male sex remains the most common cause of HCV spread in China and Vietnam .…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic screening for other STIs during medical visits for anogenital warts helps doctors identify common yet asymptomatic co-infecting diseases that would have otherwise been overlooked and under-reported by patients. While opportunistic screening is oftentimes applied for patients from high-risk groups, [21][22][23][24][25][26][27][28][29]33,34 expanding this procedure for men and women newly diagnosed with anogenital warts can improve treatment and care for patients in China. This approach enables Chinese doctors to follow international protocols of screening non-high-risk populations consistent with other low-and-middle 8,37 as well as highincome 5,9,31,36 countries.…”
Section: Resultsmentioning
confidence: 99%
“…In reviewing research conducted in China from data collected between 1998 and 2017 on STI co-infections, we find that the majority of studies target MSM, FSWs, HIV-positive, and HIV high-risk populations. 7,13,[21][22][23][24][26][27][28]33,34 However, among all of these studies, only one study dating from 1998 tested for co-infection with genital warts. 26 Among studies of MSM and HIV high-risk populations, the most common set of co-infections examined were HIV with syphilis and HIV with HSV-2, with only a handful of studies broadening the scope of co-infecting illnesses.…”
Section: Expanding Screening Of Stis For Larger Segments Of the Populmentioning
confidence: 99%